Ileal perforation-etiopathology and outcome – An observational study - Prabal Kanti Mandal; Joy Roy; Somnath Biswas; Arunima Mukhopadhyay (Asian Journal of Medical Sciences, 2024)
Background: Ileal perforations have a diverse etiology and often present with perforative peritonitis in the surgical emergency. This study is based on the scenario of management of ileal perforation encountered in a tertiary teaching hospital in West Bengal. Aims and Objectives: The aim and objective of this study is to document and evaluate the post-operative outcome based on the diverse etiopathology, clinical presentation, and surgical management performed in patients having ileal perforation. Materials and Methods: A prospective cross-sectional observational study was conducted in the Deben Mahata Government Medical College, Purulia, West Bengal, for a period of 2 years from February 2020 to January 2022 with 60 patients introperatively diagnosed with ileal perforation. Emergency exploratory laparotomy was done in all the cases presenting with perforative peritonitis. Ileal perforation was identified and an edge biopsy was taken. Appropriate surgical treatment in the forms of primary repair/resection-anastomosis/resection-ileostomy was done. The histopathological report was reviewed following surgery. The patients were evaluated in the post-operative period for post-operative morbidity and mortality. Results: Typhoid fever (68.33%) was the predominant cause in our study. The most common symptoms were abdominal pain (93%), fever (85%), and abdominal distension (75%). Widal test was performed preoperatively and was positive in 41 cases (68.33%). In our study, primary repair (58.33%), resection-anastomosis (15%), and resection-ileostomy (26.67%) were the main surgical treatment performed. Sepsis, surgical site infections (SSIs), fecal fistula, and wound dehiscence were the common post-operative complications found. Among them, SSI (51.67%) was the most common post-operative complication (P<0.0001) found and fecal fistula was the most dreaded post-operative complication with 50% mortality. Histopathological reports following surgery showed cases were mainly due to enteric fever (51.67%) and tuberculosis (25%). Conclusion: Early surgical intervention was the mainstay of treatment of ileal perforation. Delayed presentation of perforation is responsible for the development of surgical site infections (SSIs). Uncontrolled generalized sepsis, wound dehiscence, and fecal fistula were the main causes of post-operative mortality.